Systematic Review On Graphic Art With Special Reference To Historical Aspects (Journal of Namibian Studies : History Politics Culture, 2023)
Popular prints made available to the general public are the main focus of the conversation.  It aims to uncover a muted, subtle, and closely tied modernist ancestry to society's everyday cultural activities, while also presenting a comprehensive and thorough history of Bengali graphic art—a task that prominent historians have already accomplished with great success. Modernism is an artistic attempt to reestablish aesthetic interaction with the general population rather than the aversion culture, which achieves its independence and purity by severing all ties between art and life. By understanding modernism in the context of colonialism and looking at how artists used modern graphic art brought to Bengal in the eighteenth century as a potent means of self-expression while retaining its communicative potential, one can better appreciate the expansive and flexible definition of modernism. In this article, systematic review on graphic art with special reference to historical aspects has been discussed.